A simplified general circulation model for a baroclinic ocean with topography. Part I: Theory, waves and wind-driven circulations - Olbers, Dirk; Eden, C. (2003)
A new type of ocean circulation model is described and tested for various simplewind-driven circulation problems. The model resides on the vorticity balance ofthe depth averaged velocity and a hierarchy of balance equations for thevertical moments of baroclinic velocity and density, the lowest density momentbeing the baroclinic potential energy. The latter is the most importantdynamical link between the barotropic and the baroclinic motion in the presenceof a sloping topography. We derive a coupled hierarchy of tendency equations forthe potential energy and higher order density moments which, together withmoments for the baroclinic velocities and an appropriate truncation and thebarotropic vorticity balance yields in a simplified set of vertical integratedequations describing the BARotropic-Baroclinic-Interaction (BARBI) of motions inthe ocean. Using a numerical implementation of BARBI, idealized companionexperiments with a full primitive equation model (MOM) show that wavepropagation properties and baroclinic adjustments are correctly represented inBARBI in mid latitudes as well as in equatorial latitudes. Furthermore, a set ofexperiments with a realistic application to the Atlantic/Southern Ocean systemreadily reveals important aspects which have been previously reported by studiesof gyre circulations and circumpolar currents using full primitive equationmodels.